THE ALCHEMIST - Bortesi Longhi, Luis (2009)
In the financial world are tested tools and more sophisticated procedures that are sometimes incomprehensible for its impressive level of abstraction. If you have the money itself is an invention that involves a step toward dematerialization, in the contemporary economy dematerialization reaches extreme limits and the finance becomes a pure and simple «book-entry form». This article refers to the various powers and ways for governments to create «wealth» artificially and is motivated in particular by the recent international financial crisis and the reaction particularly taken by the United States.